40.4k views
5 votes
Use the graphs of functions f and g to answer the problem. (f-g)(2)

Use the graphs of functions f and g to answer the problem. (f-g)(2)-example-1
User Heap
by
4.7k points

1 Answer

5 votes

In order to find (f-g)(2), we need to find using the graphs given the next values

when x=0 we need to find the value of the function that it will be the y-coordinate

f(2)=1

g(2)=2

then for (f-g)(2)


\mleft(f-g\mright)\mleft(2\mright)=f(2)-g(2)=1-2=-1

ANSWER

(f-g)(2)=-1

User Ivan Black
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.